Pro Windows PowerShell - Deshev, Hristo (Springer, 2017)
Windows power users have always envied their friends running UNIX machines for the ease of automation that they enjoy. The traditional Windows command–line shell, cmd.exe, has never been up to par with shells like bash or tcsh, especially when it comes to text processing and process automation.